An etiology of human modernity - Bednarik, Robert G. (Anthropological Review, 2021)
Following the refutation of the replacement hypothesis, which had proposed that a ‘superior’ hominin species arose in Africa and replaced all other humans existing at the time, the auto-domestication hypothesis remains the only viable explanation for the relatively abrupt change from robust to gracile humans in the Late Pleistocene. It invokes the incidental institution of the domestication syndrome in humans, most probably by newly introduced cultural practices. It also postulates that the induction of exograms compensated for the atrophy of the brain caused by domestication. This new explanation of the origins of modernity in humans elucidates practically all its many aspects, in stark contrast to the superseded replacement hypothesis, which explained virtually nothing. The first results of the domestication syndrome’s genetic exploration have become available in recent years, and they endorse the human self-domestication hypothesis.